Empirical essays on corporate political responsibility - Ali, Hesham (2022)
Corporate social responsibility (CSR) is hardly a new concept, but corporate political responsibility (CPR) is still fledgling and growing. As such, our understanding of factors shaping CPR is limited. This thesis contains three essays that examine the antecedents of CPR, proxied through political spending disclosure (PSD), in S&P 500 firms and deepens our understanding of drivers of CPR.